GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Inference for stationary Log-Gaussian Cox point processes using Bayesian deep learning: Application to human oral microbiome image data - Shuwan Wang; Christopher K. Wikle; Athanasios C. Micheas; Jessica L. Mark Welch; Jacqueline R. Starr; Kyu Ha Lee (Spatial Statistics, 2026)

From coconut water to hydrophobic three-dimensional carbon aerogels: A recyclable and sustainable platform for oil recovery - Phuoc M. Huynh; Vy N.T. Nguyen; Quan H. Nguyen; Duy K. Trang; Phu V. Luu; Khoi M. Tran; Thanh C. Ly; Kien A. Le; Anh N. Pham; Khanh H.M. Tran; Phuoc H. Ho; Huy X. Le; et al. (Bioresource Technology Reports, 2026)

Influence of herd and environmental factors and phenotypic trends in productive and reproductive traits in dairy farms in Argentina - MJ Beribe; HA Carignano; M Piccardi; G Tuñon; M Bertossi; M Weber; D Pipino; C Sola; PR Marini; N López-Villalobos (Tropical Animal Health and Production, 2026)
Argentina hosts a wide range of dairy production systems, from pasture-based to confined models. Despite this diversity, genetic improvement has relied almost exclusively on imported semen from high-merit Holstein bulls. Unregistered Holstein populations managed under pasture-based systems account for a substantial share of national milk production, yet their productive and reproductive performance remains poorly documented. To address this gap, this study evaluated the effects of herd and environmental factors on production and fertility traits and assessed recent phenotypic trends in pasture-based dairy herds. The dataset comprised 46,588 lactations from 19,936 cows across 16 commercial herds recorded between 2010 and 2023. Traits analyzed included 305-day milk, fat and protein yields, calving-to-first-service interval, days open and calving-to-calving interval. Herd, lactation number, calving month and calving year significantly affected all traits ( p ≤ 0.0001). Peak milk yield occurred between the third and fifth lactations, while reproductive performance declined with increasing parity. Cows calving in autumn–winter (May–August) showed superior production and fertility, coinciding with months exhibiting fewer number of days with temperature–humidity index values above the heat-stress threshold. Variance component analysis indicated that cow effects explained 16–19% of the variance in production traits and 8–11% in fertility traits. Phenotypic overall trends suggested stabilization in milk yield and limited progress in fertility, although more favourable trends were observed during 2020–2023. While these recent improvements may reflect changes in herd-level conditions over time, potential genetic contributions cannot be ruled out. In pasture-based systems, the expression of imported high-merit genetics may differ across environmental conditions, underscoring the potential value of breeding programs adapted to local production conditions.

Enhanced sulfate radical generation through bimetallic Ni–Cu catalysts synthesized in a fluidized bed for rapid RB5 degradation - P. Družaitė; D. Martuzevičius; T.-H. Ha; M.-C. Lu (International Journal of Environmental Science and Technology, 2026)
The treatment of dye-containing wastewater remains a significant environmental challenge, as persistent azo dyes such as Reactive Black 5 (RB5) are resistant to conventional oxidation and biological processes. In this study, we propose a Fe-free advanced oxidation strategy based on sodium persulfate activation using Ni–Cu bimetallic catalysts synthesized via fluidized-bed homogeneous crystallization (FBHC), with a systematic comparison to catalysts prepared by conventional jar-test precipitation (JAR). The novelty of this work lies in coupling FBHC synthesis with persulfate activation to produce highly reactive, amorphous Ni–Cu catalysts capable of rapid pollutant degradation under near-neutral conditions, thereby overcoming the sludge generation and pH limitations associated with traditional Fenton systems. Using 100 mg L −1 RB5 as a model contaminant, the FBHC-derived catalyst achieved > 90% decolorization within 10 min and 70.7% TOC removal within 5 min, significantly outperforming the JAR-derived material. Kinetic analysis indicated that the degradation followed the Langmuir–Hinshelwood model, suggesting a surface-controlled reaction pathway. Radical scavenging and EPR analyses identified SO 4 · − and 1 O 2 as the dominant reactive species, with minor contributions from ·OH and negligible involvement of O 2 · − . Overall, this study demonstrates that (i) FBHC is an effective method for fabricating highly reactive bimetallic catalysts and (ii) the Ni–Cu/persulfate system represents a rapid, Fe-free oxidation process operable under mild pH conditions, offering a promising strategy for efficient and scalable textile wastewater treatment.

Mechanisms of Strong Hearts, Healthy Communities-2.0 Effects on Weight: A Mediation Analysis - Chad D. Rethorst; Margaret Demment; Meredith L. Graham; Seungyeon Ha; Alexandra L. MacMillan Uribe; Brian K. Lo; Jacob Szeszulski; Phrashiah Githinji; David Strogatz; Sara C. Folta; Miriam E. Nelson; Rebecca A. Seguin-Fowler (Journal of Nutrition Education and Behavior, 2026)

Stable yet hydrophilic graphene oxide nanomembranes by zwitterionic reduction for dye desalination - Sagnik Das; Ziwen Zhang; Erda Deng; Emmanuel M. Nsengiyumva; Ruveen Dias; Shixian Ha; Xiao Tong; Gbassey S.A. Oteme; Shweta Singh; Kai Chen; Prathima C. Nalam; Chang-Yong Nam; et al. (Chemical Engineering Journal, 2026)

Novel sensory epithelial topography of the olfactory lamellae in southern bluefin tuna, Thunnus maccoyii (Scombridae) - Myoung-Hoon Ha; Travis Dutka; Julian Pepperell; Lucille Chapuis; Caroline C. Kerr; Shaun P. Collin (Ichthyological Research, 2026)
The arrangement of the sensory epithelium over the surface of the olfactory lamellae in teleosts is variable, with a diverse pattern ranging from large expanses of continuous epithelium to numerous discrete islets. As the olfactory epithelium is the location where water-borne odorants interact with olfactory receptors, its spatial distribution pattern serves as an important anatomical proxy for olfactory ability. However, nothing is known about the olfactory epithelial pattern in southern bluefin tuna, Thunnus maccoyii . Scanning electron microscopy was used to examine the spatial distribution pattern, area, and number of olfactory epithelial patches over the olfactory lamellar surface within the olfactory rosettes of both juvenile and mature T. maccoyii . Juvenile T. maccoyii exhibit a novel olfactory epithelial topography, where the lamellae in the caudal parts of the olfactory rosette display a combination of Type IV (olfactory epithelium arranged into numerous, small discrete islets) and Type III (olfactory epithelium irregularly intermingled with non-sensory epithelium) topographies. The lamellae in the rostral parts of the olfactory rosettes primarily have Type IV topography. In both arrangement patterns, the olfactory epithelia are smaller and more numerous rostrally. In mature T. maccoyii , the Type IV topography disappears, and lamellae in all parts of the olfactory rosette display exclusively Type III topography. The combined results of this study reveal a new and unique distribution pattern of olfactory sensory epithelia in T. maccoyii , with a striking change in distribution pattern associated with both lamellar location and growth, indicating adaptation to the different hydrodynamic conditions.

Proceedings of the 2024 FDA-CRCG Workshop: Scientific and Regulatory Considerations for Assessment of Immunogenicity Risk for Generic Peptide and Oligonucleotide Drug Products - Jennifer K. Lee; Ha-Na Lee; Sudhir Agrawal; Joseph A. Balsamo; Andrew Clerman; Sofie Denies; Anne De Groot; Jeremy Fry; Nicolas Gaudenzio; Andrew J. Graves; Kristina E. Howard; SuJin Hwang; et al. (The AAPS Journal, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Hydrodynamic flow in the peripheral olfactory system of pelagic fishes: A comparison between southern bluefin tuna, Thunnus maccoyii and black marlin, Istiompax indica - Myoung-Hoon Ha; Travis Dutka; Julian Pepperell; Lucille Chapuis; Caroline C. Kerr; Shaun P. Collin (Zoology, 2026)

Development and Evaluation of a Planetary Health Diet Index: The Mediators of Atherosclerosis in South Asians Living in America Study - Nilendra K. Nair; Linh P. Bui; Caleigh M. Sawicki; Namratha R. Kandula; Alka M. Kanaya; Kyu Ha Lee; Meir Stampfer; Walter C. Willett; Shilpa N. Bhupathiraju (Journal of the Academy of Nutrition and Dietetics, 2026)

Corrigendum to “Enhanced recovery of lead and nitrate via fluidized-bed reactor: Recovery of insoluble salts from simulated gold cyanidation effluent” [Chem. Eng. J. 524 (2025), 169101] - Glyzel Ann C. Madlangbayan; Khyle Glainmer N. Quiton; Thi-Hanh Ha; Ming-Chun Lu (Chemical Engineering Journal, 2025)

Enhanced recovery of lead and nitrate via fluidized-bed reactor: Recovery of insoluble salts from simulated gold cyanidation effluent - Glyzel Ann C. Madlangbayan; Khyle Glainmer N. Quiton; Thi-Hanh Ha; Ming-Chun Lu (Chemical Engineering Journal, 2025)

Opportunities to better integrate inland fish and fisheries in multilateral environmental agreements - Abigail J. Lynch; Devin Bartley; T. Douglas Beard, Jr.; Gabriel Borba; Steven J. Cooke; Ian G. Cowx; Vittoria Elliott; Holly Embke; Edith Gondwe; Zeb Hogan; Jonathan G. Low; Jamie C. Madden; et al. (Environmental Science & Policy, 2025)

12/15-Lipooxygenase Inhibition Reduces Microvessel Constriction and Microthrombi After Subarachnoid Hemorrhage in Mice - Ari Dienel; Sung Ha Hong; Hussein A. Zeineddine; Sithara Thomas; Shafeeque C. M.; Dania A. Jose; Kiara Torres; Jose Guzman; Andrew Dunn; P. Kumar T.; Gadiparthi N. Rao; Spiros L. Blackburn; et al. (Translational Stroke Research, 2025)

Characterization and quantification of atmospheric emissions of dioxins, dl-PCBs and polycyclic aromatic hydrocarbons from municipal solid waste open burning in Southeast Asia - Nguyen Thi Kim Oanh; Chirasuda Thiemjarat; Pannawee Mekwichai; Nguyen Thanh Hang; Didin Agustian Permadi; Judith C. Chow; Thai Ha Vinh (Waste Management, 2025)

Cross-cultural evidence that intergroup conflict heightens preferences for dominant leaders: A 25-country study - Lasse Laustsen; Xiaotian Sheng; M. Ghufran Ahmad; Laith Al-Shawaf; Benjamin Banai; Irena Pavela Banai; Michael Barlev; Nicolas Bastardoz; Alexander Bor; Joey T. Cheng; Anna Chmielińska; Alexandra Cook; et al. (Evolution and Human Behavior, 2025)

The function of love: A signaling-to-alternatives account of the commitment device hypothesis - Benjamin Gelbart; Kathryn V. Walter; Daniel Conroy-Beam; Casey Estorque; David M. Buss; Kelly Asao; Agnieszka Sorokowska; Piotr Sorokowski; Toivo Aavik; Grace Akello; Mohammad Madallh Alhabahba; Charlotte Alm; et al. (Evolution and Human Behavior, 2025)

Prime editing via precise sequence insertion restores function of the recessive rc allele in rice - Cuong X. Nguyen; Trong D. Nguyen; Thao T. Dinh; Linh T. Nguyen; Linh K. Ly; Ha H. Chu; Thang C. La; Phat T. Do (Plant Cell Reports, 2025)

Biometry, hatching efficiency, growth performance and survival of the brine shrimp Artemia franciscana from Tanzania - AT Jacob; IB Kapinga; AP Mwijage; A Luvanga; A Mremi; C Sekadende; SS Shaban; HA Lamtane; AB Matondo (African Journal of Marine Science, 2025)

Development and use of DJ-1 affinity microcolumns to screen and study small drug candidates for Parkinson's disease - Jacob C. Jones; Jiusheng Lin; Sadia Sharmeen; Md Masudur Rahman; Ha H. Truong; Ting-Rong Chern; Mark A. Wilson; David S. Hage (Analytica Chimica Acta, 2025)

Challenging the Standard Immunogenicity Assessment Approach: 1-Tiered ADA Testing Strategy in Clinical Trials - Ching-Ha Lai; Mu Chen; Sasha Fraser; Jessica Wang; Sean McAfee; Emma Speaks; Nicholas Simeone; Jacqueline Rodriguez; Colin Stefan; Lisa DeStefano; Chinnasamy Elango; Matthew D. Andisik; et al. (The AAPS Journal, 2024)

Architecture, light, and circadian biology: A scoping review - Philip Lewis; Rania Christoforou; Peiman Pilehchi Ha; Ursula Wild; Marcel Schweiker; Thomas C. Erren (Science of The Total Environment, 2024)

Exploring the feasibility of using fluidized bed homogeneous crystallization technology to recover sulfate ions from briny water as calcium sulfate pellets - Hun-Yi Liu; Anabella C. Vilando; Thi-Hanh Ha; Ming-Chun Lu (Desalination, 2024)

BNST CRF receptor type 1 modulates mechanical hypersensitivity induced by adolescent alcohol exposure in adult female mice - Natalia B. Bertagna; Eleanor B. Holmgren; Sheila A. Engi; Linh Ha; Fabio C. Cruz; Lucas Albrechet-Souza; Tiffany A. Wills (Psychopharmacology, 2024)

Correction to: Neutralizing Antibody Sample Testing and Report Harmonization - Darshana Jani; Michele Gunsior; Robin Marsden; Kyra J. Cowan; Susan C. Irvin; Laura Schild Hay; Bethany Ward; Luke Armstrong; Mitra Azadeh; Liching Cao; Rebecca Carmean; Jason DelCarpini; et al. (The AAPS Journal, 2024)

Understanding predictors of mistletoe infection across an urban university campus in Southwest China - Yuchen Niu; Benjamin Laffitte; Sophia Zuoqiu; Barnabas C. Seyler; Zhengang Ha; Jianan Chen; Lei Chen; Ya Tang (Urban Ecosystems, 2024)
Due to the importance of trees in urban ecosystems, it is crucial to understand the distribution, prevalence, and intensity of parasitic mistletoe infection across urban landscapes. In this study, we aimed to understand how various tree-related factors (e.g., tree taxonomy, size, pruning history, nativity, foliage, density, and diversity) might influence mistletoe prevalence and infection intensity across a typical subtropical urban greenspace. We surveyed 6,012 trees representing 96 species, 76 genera, and 44 families across a large, urban university campus in a major Southwest Chinese city. In total, we found 353 mistletoe host trees (prevalence: 5.87%), largely concentrated on the eastern part of campus, partially due to the proximity of waterbodies and a large adjacent greenspace, as well as higher tree density. To understand how predictors affected the prevalence and intensity of mistletoe infection, we used a hurdle model fitting our zero-inflated count data. Four independent variables significantly affected the prevalence of mistletoe infestation, with three demonstrating positive correlations (crown width, tree density, and tree diversity). One variable (evergreen foliage) negatively correlated with mistletoe prevalence. However, only one factor was found to significantly affect mistletoe infection intensity (crown width, positively). Due to the variety of ecosystem services mistletoes provide, more studies are necessary to assess the impact of various mistletoe management strategies, especially on urban biodiversity.

Neutralizing Antibody Sample Testing and Report Harmonization - Darshana Jani; Michele Gunsior; Robin Marsden; Kyra J. Cowan; Susan C. Irvin; Laura Schild Hay; Bethany Ward; Luke Armstrong; Mitra Azadeh; Liching Cao; Rebecca Carmean; Jason DelCarpini; et al. (The AAPS Journal, 2024)
Immunogenicity testing and characterization is an important part of understanding the immune response to administration of a protein therapeutic. Neutralizing antibody (NAb) assays are used to characterize a positive anti-drug antibody (ADA) response. Harmonization of reporting of NAb assay performance and results enables efficient communication and expedient review by industry and health authorities. Herein, a cross-industry group of NAb assay experts have harmonized NAb assay reporting recommendations and provided a bioanalytical report (BAR) submission editable template developed to facilitate agency filings. This document addresses key bioanalytical reporting gaps and provides a report structure for documenting clinical NAb assay performance and results. This publication focuses on the content and presentation of the NAb sample analysis report including essential elements such as the method, critical reagents and equipment, data analysis, study samples, and results. The interpretation of immunogenicity data, including the evaluation of the impact of NAb on safety, exposure, and efficacy, is out of scope of this publication. Graphical Abstract

Effects of water-table changes following rainfall events on arsenic fate and transport in groundwater–surface water mixing zones - Jonghoon Park; Dongyeop Lee; Ha Kim; Nam C. Woo (Science of The Total Environment, 2024)

Precipitation frequency in Med-CORDEX and EURO-CORDEX ensembles from 0.44° to convection-permitting resolution: impact of model resolution and convection representation - Minh T. Ha; Sophie Bastin; Philippe Drobinski; L. Fita; J. Polcher; O. Bock; M. Chiriaco; D. Belušić; C. Caillaud; A. Dobler; J. Fernandez; K. Goergen; et al. (Climate Dynamics, 2024)
Recent studies using convection-permitting (CP) climate simulations have demonstrated a step-change in the representation of heavy rainfall and rainfall characteristics (frequency-intensity) compared to coarser resolution Global and Regional climate models. The goal of this study is to better understand what explains the weaker frequency of precipitation in the CP ensemble by assessing the triggering process of precipitation in the different ensembles of regional climate simulations available over Europe. We focus on the statistical relationship between tropospheric temperature, humidity and precipitation to understand how the frequency of precipitation over Europe and the Mediterranean is impacted by model resolution and the representation of convection (parameterized vs. explicit). We employ a multi-model data-set with three different resolutions (0.44°, 0.11° and 0.0275°) produced in the context of the MED-CORDEX, EURO-CORDEX and the CORDEX Flagship Pilot Study "Convective Phenomena over Europe and the Mediterranean" (FPSCONV). The multi-variate approach is applied to all model ensembles, and to several surface stations where the integrated water vapor (IWV) is derived from Global Positioning System (GPS) measurements. The results show that all model ensembles capture the temperature dependence of the critical value of IWV (IWVcv), above which an increase in precipitation frequency occurs, but the differences between the models in terms of the value of IWVcv, and the probability of its being exceeded, can be large at higher temperatures. The lower frequency of precipitation in convection-permitting simulations is not only explained by higher temperatures but also by a higher IWVcv necessary to trigger precipitation at similar temperatures, and a lower probability to exceed this critical value. The spread between models in simulating IWVcv and the probability of exceeding IWVcv is reduced over land in the ensemble of models with explicit convection, especially at high temperatures, when the convective fraction of total precipitation becomes more important and the influence of the representation of entrainment in models thus becomes more important. Over lowlands, both model resolution and convection representation affect precipitation triggering while over mountainous areas, resolution has the highest impact due to orography-induced triggering processes. Over the sea, since lifting is produced by large-scale convergence, the probability to exceed IWVcv does not depend on temperature, and the model resolution does not have a clear impact on the results.

Tris(1,3-dichloro-2-propyl) phosphate disrupts cellular metabolism within human embryonic kidney (HEK293) cells - Sarah Avila-Barnard; Megan Ha; Charvita Nemarugommula; Jenna L. Wiegand; Haiyan Ke; Amancio De Souza; Rachel Behar; David C. Volz (Journal of Hazardous Materials, 2024)

Citizen scientists’ engagement in flood risk-related data collection: a case study in Bui River Basin, Vietnam - Huan N. Tran; Martine Rutten; Rajaram Prajapati; Ha T. Tran; Sudeep Duwal; Dung T. Nguyen; Jeffrey C. Davids; Konrad Miegel (Environmental Monitoring and Assessment, 2024)
Time constraints, financial limitations, and inadequate tools restrict the flood data collection in undeveloped countries, especially in the Asian and African regions. Engaging citizens in data collection and contribution has the potential to overcome these challenges. This research demonstrates the applicability of citizen science for gathering flood risk-related data on residential flooding, land use information, and flood damage to paddy fields for the Bui River Basin in Vietnam. Locals living in or around flood-affected areas participated in data collection campaigns as citizen scientists using self-investigation or investigation with a data collection app, a web form, and paper forms. We developed a community-based rainfall monitoring network in the study area using low-cost rain gauges to draw locals’ attention to the citizen science program. Fifty-nine participants contributed 594 completed questionnaires and measurements for four investigated subjects in the first year of implementation. Five citizen scientists were active participants and contributed more than 50 completed questionnaires or measurements, while nearly 50% of citizen scientists participated only one time. We compared the flood risk-related data obtained from citizen scientists with other independent data sources and found that the agreement between the two datasets on flooding points, land use classification, and the flood damage rate to paddy fields was acceptable (overall agreement above 73%). Rainfall monitoring activities encouraged the participants to proactively update data on flood events and land use situations during the data collection campaign. The study’s outcomes demonstrate that citizen science can help to fill the gap in flood data in data-scarce areas.

Quantifying Disturbance and Recovery in Estuaries: Tropical Cyclones and High-Frequency Measures of Oxygen and Salinity - C. D. Buelo; A. F. Besterman; J. A. Walter; M. L. Pace; D. T. Ha; S. J. Tassone (Estuaries and Coasts, 2024)

Encapsulation of Triphasia trifolia extracts by pH and thermal dual-sensitive chitosan hydrogels for controlled release - Nga H.N. Do; Tuan N.A. Huynh; Tien X. Le; Anh C. Ha; Phung K. Le (Carbohydrate Polymers, 2023)

Betaproteobacteria are a key component of surface water biofilters that maintain sustained manganese removal in response to fluctuations in influent water temperature - N.E. McCormick; M. Earle; A. Kent; C. Ha; L. Hakes; L. Anderson; A.K. Stoddart; M.G.I. Langille; G.A. Gagnon (Water Research, 2023)

Remediation of arsenic contaminated water and soil using mechanically (ball milling) activated and pyrite-amended electrolytic manganese slag - Zhihao Ha; Mengyu Ma; Xiaohan Tan; Yanxin Lan; Yanmin Lin; Tian C. Zhang; Dongyun Du (Environmental Research, 2023)

Triphenyl phosphate-induced pericardial edema in zebrafish embryos is reversible following depuration in clean water - Jenna Wiegand; John Hoang; Sarah Avila-Barnard; Charvita Nemarugommula; Megan Ha; Sharon Zhang; Heather M. Stapleton; David C. Volz (Aquatic Toxicology, 2023)

Using tree rings to detect a CO2 fertilization effect: a global review - Benjamin Laffitte; Barnabas C. Seyler; Pengbo Li; Zhengang Ha; Ya Tang (Trees, 2023)

Manipulation of photoperiod induces fat storage, but not fat mobilization in the migratory songbird, Dumetella carolinensis (Gray Catbird) - Abigail C. Valachovic; Jussara N. Chaves; Kristen J. DeMoranville; Taylor Garbenis; Boi Minh Ha Nguyen; Michael Hughes; Janice M. Huss; Paul J. Schaeffer (Journal of Comparative Physiology B, 2023)

Emerging and Legacy Pollutants in Vietnam Related to the Climate–Water–Energy–Food Nexus - Duc Huy Dang; Margaret C. Graham; Quang Khai Ha (Archives of Environmental Contamination and Toxicology, 2023)

Vertical distributions of organic matter components in sea ice near Cambridge Bay, Dease Strait, Canadian Archipelago - Kwanwoo Kim; Sun-Yong Ha; Kyung-Hoon Shin; Jee-Hoon Kim; C. J. Mundy; Laura A. Dalman; Bo Kyung Kim; Dabin Lee; Hyo Keun Jang; Yejin Kim; Sanghoon Park; Sang Heon Lee (Frontiers in Marine Science, 2023)
Ice algae thriving within sea ice play a crucial role in transferring energy to higher trophic levels and influencing biogeochemical processes in polar oceans; however, the distribution of organic matter within the ice interior is not well understood. This study aimed to investigate the vertical distribution of organic matter, including chlorophyll a (Chl-a), particulate organic carbon and nitrogen (POC and PON), carbohydrates (CHO), proteins (PRT), lipids (LIP), and food material (FM), within the sea ice. Samples were collected from the bottom, middle, and top sections of the sea ice column near Cambridge Bay during the spring of 2018. Based on the δ 13 C signature, biochemical composition, and POC contribution of biopolymeric carbon (BPC), the organic substances within the sea ice were predominantly attributed to marine autotrophs. While the highest concentrations of each parameter were observed at the sea ice bottom, notable concentrations were also found in the upper sections. The average sea ice column-integrated Chl- a concentration was 5.05 ± 2.26 mg m −2 , with the bottom ice section contributing 59% (S.D. = ± 10%) to the total integration. The column-integrated concentrations of FM, BPC, POC, and PON were 2.05 ± 0.39, 1.10 ± 0.20, 1.47 ± 0.25, and 0.09 ± 0.03 g m −2 , respectively. Contributions of the bottom ice section to these column-integrated concentrations varied for each parameter, with values of 20 ± 6, 21 ± 7, 19 ± 5, and 28 ± 7%, respectively. While the bottom ice section exhibited a substantial Chl- a contribution in line with previous studies, significantly higher contributions of the other parameters were observed in the upper sea ice sections. This suggests that the particulate matter within the interior of the sea ice could potentially serve as an additional food source for higher trophic grazers or act as a seeding material for a phytoplankton bloom during the ice melting season. Our findings highlight the importance of comprehensive field measurements encompassing the entire sea ice section to better understand the distribution of organic carbon pools within the sea ice in the Arctic Ocean.

A novel passivator based on electrolytic manganese residues and calcite for arsenic sorption and heavy metal passivation of contaminated soil - Mengyu Ma; Zhihao Ha; Chenyang Lv; Xiangqun Xu; Changyi Li; Dongyun Du; Tian C. Zhang; Ruan Chi (Journal of Cleaner Production, 2023)

Synopsis of myxosporean species (Cnidaria: Myxozoa) parasitizing fishes from Vietnam - Nguyen Ngoc Chinh; Nguyen Thi Hoang Ha; Pham Ngoc Doanh; Jorge C. Eiras; Christopher M. Whipps; Sho Shirakashi (Systematic Parasitology, 2023)

Improvement of anti-tyrosinase activity in potential skin whitening products by combining herbal extracts and reducing their tannin content by collagen fibre adsorption - Anh C. Ha; Tan M. Le (South African Journal of Botany, 2023)

Global assessment of chemical quality of drinking water: The case of trihalomethanes - Cristina M Villanueva; Iro Evlampidou; Fathelrahman Ibrahim; Carolina Donat-Vargas; Antonia Valentin; Anca-Maria Tugulea; Shinya Echigo; Dragana Jovanovic; Albert T Lebedev; Mildred Lemus-Pérez; Manuel Rodriguez-Susa; Arben Luzati; et al. (Water Research, 2023)

From the basics to emerging diagnostic technologies: What is on the horizon for tilapia disease diagnostics? - Ha Thanh Dong; Thawatchai Chaijarasphong; Andrew C. Barnes; Jérôme Delamare‐Deboutteville; Peiyu Alison Lee; Saengchan Senapin; Chadag Vishnumurthy Mohan; Kathy F. J. Tang; Sharon E. McGladdery; Melba G. Bondad‐Reantaso (Reviews in Aquaculture, 2023)
Tilapia is an affordable protein source farmed in over 140 countries with the majority of production in low‐ and middle‐income countries. Intensification of tilapia farming has exacerbated losses caused by emerging and re‐emerging infectious diseases. Disease diagnostics play a crucial role in biosecurity and health management to mitigate disease loss and improve animal welfare in aquaculture. Three continuous levels of diagnostics (I, II and III) for aquatic species have been proposed by Food and Agriculture Organization of the United Nations (FAO) and the Network of Aquaculture Centers in Asia and the Pacific (NACA) to promote the integration of basic and advanced methods to achieve accurate and meaningful interpretation of diagnostic results. However, the recent proliferation of cutting‐edge molecular methods applied in the diagnosis of diseases of aquacultured animals has shifted the focus of researchers and users away from basic approaches and toward molecular diagnostics, despite the fact that many diseases can be rapidly diagnosed using inexpensive, simple microscopic examination and that most emerging diseases in aquaculture were discovered by histopathology. This review, therefore, revisits and highlights the importance of the three levels of diagnostics for diseases of tilapia, particularly the frequently overlooked basic procedures (e.g., case history records, gross pathology, presumptive diagnostic methods and histopathology). The review also covers current and emerging molecular diagnostic technologies for tilapia pathogens including polymerase chain reaction methods (conventional, quantitative, digital), isothermal amplification methods Loop‐mediated Isothermal Amplification (LAMP), recombinase polymerase amplification (RPA), clustered regularly interspaced short palindromic repeats (CRISPR)‐based detection, lateral flow immunoassays, as well as discussing what is on the horizon for tilapia disease diagnostics (next generation sequencing, artificial intelligence, environmental Deoxyribonucleic Acid (DNA) and Ribonucleic Acid (RNA) and point‐of‐care testing) providing a future vision for transferring these technologies to farmers and stakeholders for a sustainable aquatic food system transformation.

Effects of dry and heavy rainfall periods on arsenic species and behaviour in the aquatic environment adjacent a mining area in South Korea - Jonghoon Park; Dongyeop Lee; Ha Kim; Nam C. Woo (Journal of Hazardous Materials, 2023)

The relationship between feline-ality™, the interpersonal circumplex, and cat characteristics - Saethra Darling; James C. Ha (Applied Animal Behaviour Science, 2023)

Strategies for utilization of crop wild relatives in plant breeding programs - Anamika Kashyap; Pooja Garg; Kunal Tanwar; Jyoti Sharma; Navin C. Gupta; Pham Thi Thu Ha; R. C. Bhattacharya; Annaliese S. Mason; Mahesh Rao (Theoretical and Applied Genetics, 2022)

Anti-drug Antibody Sample Testing and Reporting Harmonization - Darshana Jani; Robin Marsden; Michele Gunsior; Laura Schild Hay; Bethany Ward; Kyra J. Cowan; Mitra Azadeh; Breann Barker; Liching Cao; Kristin R. Closson; Kelly Coble; Sanjay L. Dholakiya; et al. (The AAPS Journal, 2022)
A clear scientific and operational need exists for harmonized bioanalytical immunogenicity study reporting to facilitate communication of immunogenicity findings and expedient review by industry and health authorities. To address these key bioanalytical reporting gaps and provide a report structure for documenting immunogenicity results, this cross-industry group was formed to establish harmonized recommendations and a develop a submission template to facilitate agency filings. Provided here are recommendations for reporting clinical anti-drug antibody (ADA) assay results using ligand-binding assay technologies. This publication describes the essential bioanalytical report (BAR) elements such as the method, critical reagents and equipment, study samples, results, and data analysis, and provides a template for a suggested structure for the ADA BAR. This publication focuses on the content and presentation of the bioanalytical ADA sample analysis report. The interpretation of immunogenicity data, including the evaluation of the impact of ADA on safety, exposure, and efficacy, is out of scope of this publication. Graphical Abstract

The distribution of mycosporine-like amino acids in phytoplankton across a Southern Ocean transect - Elliot L. Weiss; Mattias Rolf Cape; B. Jack Pan; Maria Vernet; Chase C. James; Tim J. Smyth; Sun-Yong Ha; José L. Iriarte; B. Greg Mitchell (Frontiers in Marine Science, 2022)
Interactions between phytoplankton and ultraviolet radiation (UVR: 280 – 400 nm) are undergoing changes dictated by variability in ocean temperature, the depth of mixed layers, nutrient availability, and the thickness of the ozone layer. There are a variety of mechanisms for phytoplankton to cope with UVR stress, one of the most prevalent being the presence of mycosporine-like amino acids (MAAs). Despite the importance of these molecules to phytoplankton fitness under UVR stress, knowledge of the diversity and distribution of these molecules in the world’s oceans is relatively limited. Here, the composition and distribution of MAAs in phytoplankton were examined in a transect across the Southern Ocean, crossing multiple fronts, from eastern New Zealand to the West Antarctic Peninsula in March and April of 2018. The highest concentration of MAAs (> 0.2 μg/L) was found between 50 and 60°S, as well as along a longitudinal gradient between 137.47 and 144.78°W. A strong correlation was found between a model of the preceding month’s UVR dosage experienced in the mixed layer and the ratio of MAAs to chlorophyll-a across the transect, indicating a relationship between the integrated history of light exposure and phytoplankton physiology. Haptophytes accounted for the majority of biomass north of the polar front (PF) and were strongly correlated with a diversity of MAAs. South of the PF a transition to a community dominated by diatoms was observed, with community composition changes strongly correlated to porphyra-334 concentrations. The data presented here provide a baseline for MAA abundance and association with specific phytoplankton taxa across the Southern Ocean amid a changing climate.

Autogenous vaccination in aquaculture: A locally enabled solution towards reduction of the global antimicrobial resistance problem - Andrew C. Barnes; Oleksandra Rudenko; Matt Landos; Ha Thanh Dong; Angela Lusiastuti; Le Hong Phuoc; Jerome Delamare‐Deboutteville (Reviews in Aquaculture, 2022)
Antimicrobial resistance is a global public health crisis with attention focussed on food supply as part of the ‘One Health’ integration of veterinary, environmental and public health. Aquaculture has been the fastest growing livestock sector in recent decades and is critical to nutritional security in many low‐ and middle‐income countries (LMIC). With ready access to antibiotics and limited availability of veterinary support, disease control with antibiotics is poorly informed, often unrecorded and high in many countries where aquaculture growth is fastest. Vaccination of fish in LMIC with locally produced autogenous vaccines against bacterial diseases may provide a locally driven, cost‐effective means of reducing antibiotic use, replicating the successes achieved during the growth of Norway's aquaculture industry. Autogenous vaccines, as part of an informed veterinary health programme, have several advantages in terms of intellectual property, efficacy and flexibility. We consider access to fish vaccines in example countries of high aquaculture importance, including Thailand, Vietnam and Indonesia. We contrast the success of antimicrobial reduction in Norwegian salmon aquaculture with the high antibiotic use in the Chilean industry where vaccines are available, finding that regulation, planning, husbandry and environmental problems may increase disease incidence and severity. We identify technical, bureaucratic and infrastructural transitions that could facilitate implementation of autogenous vaccination in LMIC aquaculture against challenging socio‐economic and environmental backgrounds. The benefits of autogenous vaccination to animal welfare, transboundary biosecurity, local farmer and industry economics, and to public health, favour implementation in aquaculture as a locally enabled solution to the global problem of antimicrobial resistance.

Preface to the Special Issue: Climate Change and Variability of Tropical Cyclone Activity - Liguang Wu; Bin Wang; Johnny C. L. Chan; Kyung-Ja Ha; Il-Ju Moon; Jun Matsumoto; Zhemin Tan; Ke Fan (Advances in Atmospheric Sciences, 2022)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Icariin reduces bone loss in a Rankl‐induced transgenic medaka ( Oryzias latipes ) model for osteoporosis - Cuong V. Pham; Thanh T. Pham; Thuy T. Lai; Dat C. Trinh; Huong V. M. Nguyen; Tam T. M. Ha; Thuong T. Phuong; Long D. Tran; Christoph Winkler; Thuy T. To (Journal of Fish Biology, 2021)
Given the limitations and side effects of many synthetic drugs, natural products are an important alternative source for drugs and medications for many diseases. Icariin (ICA), one of the main flavonoids from plants of the Epimedium genus, has been shown to ameliorate osteoporosis and improve bone health in preclinical studies. Those studies have used different in vivo models, mostly rodents, but the underlying mechanisms remain unclear. The present study shows, for the first time, that ICA reduces bone damage in a Rankl‐induced medaka fish ( Oryzias latipes ), a non‐rodent osteoporosis model. Live imaging was previously performed in this model to characterize antiresorptive and bone‐anabolic properties of drugs. Here, a new quantification method (I M ) was established based on the length of mineralized neural arches to quantify levels of bone mineralization damage and protection in early post‐embryonic fish. This method was validated by quantification of three levels of bone damage in three independent Rankl fish lines, and by the determination of different degrees of severity of osteoporosis‐like phenotypes in one Rankl line exposed to variable Rankl induction schemes. I M was also used to quantify the efficacy of alendronate and etidronate, two common anti‐osteoporotic bisphosphonates, and revealed comparable bone protective effects for ICA and alendronate in this fish osteoporosis model. This study's data support the value of the medaka fish model for bone research and establish a method to screen for novel osteoprotective compounds.

Financial and Institutional Support Are Important for Large-Scale Kelp Forest Restoration - Aaron M. Eger; Adriana Vergés; Chang Geun Choi; Hartvig Christie; Melinda A. Coleman; Camilla W. Fagerli; Daisuke Fujita; Masatoshi Hasegawa; Jeong Ha Kim; Mariana Mayer-Pinto; Dan C. Reed; Peter D. Steinberg; et al. (Frontiers in Marine Science, 2020)

Genome-wide analysis of brassinosteroid responsive small RNAs in Arabidopsis thaliana - So Young Park; Jae-Han Choi; Dong-Ha Oh; John C. Johnson; Maheshi Dassanayake; Dong-Hoon Jeong; Man-Ho Oh (Genes & Genomics, 2020)

Loss of vacuolar acidity results in iron-sulfur cluster defects and divergent homeostatic responses during aging in Saccharomyces cerevisiae - Kenneth L. Chen; Toby N. Ven; Matthew M. Crane; Matthew L. C. Brunner; Adrian K. Pun; Kathleen L. Helget; Katherine Brower; Dexter E. Chen; Ha Doan; Justin D. Dillard-Telm; Ellen Huynh; Yen-Chi Feng; et al. (GeroScience, 2020)

Age-related differences in diet and foraging behavior of the critically endangered Mariana Crow (Corvus kubaryi), with notes on the predation of Coenobita hermit crabs - Sarah K. Faegre; Lindsey Nietmann; Phillip Hannon; James C. Ha; Renee R. Ha (Journal of Ornithology, 2020)

Distribution of infectious endogenous retroviruses in mixed-breed and purebred cats - Minh Ha Ngo; Takehisa Soma; Hwa-Young Youn; Taiji Endo; Isaac Makundi; Junna Kawasaki; Ariko Miyake; Bui Thi To Nga; Huyen Nguyen; MaríaCruz Arnal; Daniel Fernández de Luco; R. M. C. Deshapriya; et al. (Archives of Virology, 2020)

Unpleasant Sound Elicits Negative Emotion and Reinstates Drug Seeking - Suchan Chang; Yu Fan; Joo Hyun Shin; Yeonhee Ryu; Mi Seon Kim; Scott C. Steffensen; Hyung Kyu Kim; Jin Mook Kim; Bong Hyo Lee; Eun Young Jang; Chae Ha Yang; Hee Young Kim (Molecular Neurobiology, 2019)

Estimation of size of tropical cyclones in the North Indian Ocean using Oceansat-2 scatterometer high-resolution wind products - Neeru Jaiswal; Doan Thi Thu Ha; C. M. Kishtawal (Theoretical and Applied Climatology, 2019)

Sixty years of global progress in managed aquifer recharge - P. Dillon; P. Stuyfzand; T. Grischek; M. Lluria; R. D. G. Pyne; R. C. Jain; J. Bear; J. Schwarz; W. Wang; E. Fernandez; C. Stefan; M. Pettenati; et al. (Hydrogeology Journal, 2019)

In vivo growth and genomic characterization of rickettsia‐like organisms isolated from farmed Chinook salmon ( Oncorhynchus tshawytscha ) in New Zealand - E Gias; C L Brosnahan; D Orr; B Binney; H J Ha; M A Preece; B Jones (Journal of Fish Diseases, 2018)
A rickettsia‐like organism, designated NZ ‐ RLO 2, was isolated from Chinook salmon ( Oncorhynchus tshawytscha ) farmed in the South Island, New Zealand. In vivo growth showed NZ ‐ RLO 2 was able to grow in CHSE ‐214, EPC , BHK ‐21, C6/36 and Sf21 cell lines, while Piscirickettsia salmonis LF ‐89 T grew in all but BHK ‐21 and Sf21. NZ ‐ RLO 2 grew optimally in EPC at 15°C, CHSE ‐214 and EPC at 18°C. The growth of LF ‐89 T was optimal at 15°C, 18°C and 22°C in CHSE ‐24, but appeared less efficient in EPC cells at all temperatures. Pan‐genome comparison of predicted proteomes shows that available Chilean strains of P. salmonis grouped into two clusters ( p‐ value = 94%). NZ ‐ RLO 2 was genetically different from previously described NZ ‐ RLO 1, and both strains grouped separately from the Chilean strains in one of the two clusters ( p ‐value = 88%), but were closely related to each other. TaqMan and Sybr Green real‐time PCR targeting RNA polymerase (rpoB) and DNA primase (dnaG), respectively, were developed to detect NZ ‐ RLO 2. This study indicates that the New Zealand strains showed a closer genetic relationship to one of the Chilean P. salmonis clusters; however, more Piscirickettsia genomes from wider geographical regions and diverse hosts are needed to better understand the classification within this genus.

Can the polyculture with South American catfish improve the feeding efficiency of rainbow trout culture? - Felipe Anderson Pereira; Natalia Ha; André Fernando Nascimento Gonçalves; Hélio Antunes; Wagner C. Valenti; Thiago El Hadi Perez Fabregat (Aquaculture International, 2018)

Suggested new breakpoints of anti-MERS-CoV antibody ELISA titers: performance analysis of serologic tests - J.-H. Ko; M. A. Müller; H. Seok; G. E. Park; J. Y. Lee; S. Y. Cho; Y. E. Ha; J. Y. Baek; S. H. Kim; J.-M. Kang; Y.-J. Kim; I. J. Jo; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

First report of a rickettsia‐like organism from farmed Chinook salmon, Oncorhynchus tshawytscha (Walbaum), in New Zealand - C. L. Brosnahan; H. J. Ha; K. Booth; A. M. J. McFadden; J. B. Jones (New Zealand Journal of Marine and Freshwater Research, 2017)
In the summer months of 2015 Chinook salmon, Oncorhynchus tshawytscha (Walbaum), were submitted to the New Zealand Ministry for Primary Industries (MPI) for disease investigation. Gross examination of 10 moribund fish revealed multiple areas of ulceration over all areas of the body including fins and mouth in eight of the 10 fish. Pale livers ( n = 4), mottled appearance of the kidney ( n = 5) and reddening of the distal intestines ( n = 5) were also observed. As these fish presented with skin lesions, Piscirickettsia salmonis was included as a differential diagnosis. Testing for this agent was conducted and a rickettsia ‐ like organism (RLO) was detected by histopathology in seven fish and by molecular methods in three fish. Nucleic acid sequencing revealed that this organism had highest similarity to a piscirickettsia‐like organism with a 19 base pair (bp) deletion in the internal transcribed spacer (ITS) region of the rDNA operon when compared to the reference strain P. salmonis , LF‐89 (ATCC VR‐1361). The variation was similar to that of the Tasmanian RLO detected in Atlantic salmon, Salmo salar L (GenBank accession number AY578985). Based on these sequence variations, a tentative identification of New Zealand rickettsia‐like organism (NZ‐RLO) was suggested. NZ‐RLO is not considered to be the primary cause of the mortalities in these fish, with the primary cause still under investigation. This is the first report of a RLO in New Zealand farmed salmon.

Empirical combination of a β-lactam to vancomycin may not improve outcomes of methicillin-susceptible Staphylococcus aureus bacteremia, compared to vancomycin monotherapy - G. E. Park; J.-H. Ko; S. Y. Cho; Y. E. Ha; N. Y. Lee; C.-I. Kang; D. R. Chung; J.-H. Song; K. R. Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Fine mapping of Restorer-of-fertility in pepper (Capsicum annuum L.) identified a candidate gene encoding a pentatricopeptide repeat (PPR)-containing protein - Yeong Deuk Jo; Yeaseong Ha; Joung-Ho Lee; Minkyu Park; Alex C. Bergsma; Hong-Il Choi; Sandra Goritschnig; Bjorn Kloosterman; Peter J. van Dijk; Doil Choi; Byoung-Cheorl Kang (Theoretical and Applied Genetics, 2016)

Reduction of GIGANTEA expression in transgenic Brassica rapa enhances salt tolerance - Jin A. Kim; Ha-eun Jung; Joon Ki Hong; Victor Hermand; C. Robertson McClung; Yeon-Hee Lee; Joo Yeol Kim; Soo In Lee; Mi-Jeong Jeong; Jungsun Kim; DaeJin Yun; WeoYeon Kim (Plant Cell Reports, 2016)

Revision of Metahaliotrema Yamaguti, 1953 (Monogenoidea: Dactylogyridae), with new and previously described species from the spotted scat Scatophagus argus (Linnaeus) (Perciformes: Scatophagidae) in Vietnam - Delane C. Kritsky; Ha Van Nguyen; Ngo Duy Ha; Richard A. Heckmann (Systematic Parasitology, 2016)

Piperazine derivatives as iron chelators: a potential application in neurobiology - S. Abdelsayed; N. T. Ha Duong; C. Bureau; P. P. Michel; E. C. Hirsch; J. M. El Hage Chahine; N. Serradji (BioMetals, 2015)

Generic piperacillin/tazobactam is not associated with galactomannan false-positivity in adult patients with cancer: a case–control study - J.-H. Ko; K. R. Peck; W. J. Lee; J. Y. Lee; S. Y. Cho; Y. E. Ha; C.-I. Kang; D. R. Chung; C. W. Jung; E.-S. Kang; J.-H. Song (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Risk factors for cytomegalovirus gastrointestinal diseases in adult patients with cancer - J.-H. Ko; K. R. Peck; W. J. Lee; K. Huh; J. R. Yoo; K. Kim; S. Y. Cho; Y. E. Ha; C.-I. Kang; D. R. Chung; C. W. Jung; Y.-H. Kim; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

A phylogeny of softshell turtles (Testudines: Trionychidae) with reference to the taxonomic status of the critically endangered, giant softshell turtle, Rafetus swinhoei - Minh Le; Ha T. Duong; Long D. Dinh; Truong Q. Nguyen; Peter C. H. Pritchard; Timothy McCormack (Organisms Diversity & Evolution, 2014)

Cannabinoid CB2 receptor immunolabelling in the healthy brain—still a live possibility - John C. Ashton; Yiwen Zheng; Cynthia Darlington; Jean-Ha Baek; Paul F. Smith (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Impact of a computerized alert system for bacteremia notification on the appropriate antibiotic treatment of Staphylococcus aureus bloodstream infections - J. Kim; E.-J. Joo; Y. E. Ha; S. Y. Park; C.-I. Kang; D. R. Chung; J.-H. Song; K. R. Peck (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Hypolithic microbial communities: between a rock and a hard place - Yuki Chan; Donnabella C. Lacap; Maggie C. Y. Lau; Kong Ying Ha; Kimberley A. Warren‐Rhodes; Charles S. Cockell; Donald A. Cowan; Christopher P. McKay; Stephen B. Pointing (Environmental Microbiology, 2012)
Summary Drylands are the largest terrestrial biome on Earth and a ubiquitous feature is desert pavement terrain, comprising rocks embedded in the mineral soil surface. Quartz and other translucent rocks are common and microbial communities termed hypoliths develop as biofilms on their ventral surfaces. In extreme deserts these represent major concentrations of biomass, and are emerging as key to geobiological processes and soil stabilization. These highly specialized communities are dominated by cyanobacteria that support diverse heterotrophic assemblages. Here we identify global‐scale trends in the ecology of hypoliths that are strongly related to climate, particularly with regard to shifts in cyanobacterial assemblages. A synthesis of available data revealed a linear trend for colonization with regard to climate, and we suggest potential application for hypoliths as ‘biomarkers’ of aridity on a landscape scale. The potential to exploit the soil‐stabilizing properties of hypolithic colonization in environmental engineering on dryland soils is also discussed.

Dependency of typhoon intensity and genesis locations on El Niño phase and SST shift over the western North Pacific - Kyung-Ja Ha; Soon-Jo Yoon; Kyung-Sook Yun; Jong-Seong Kug; Yeon-Soo Jang; Johnny C. L. Chan (Theoretical and Applied Climatology, 2012)

Effects of acupuncture on stress-induced relapse to cocaine-seeking in rats - Seong Shoon Yoon; Eun Jin Yang; Bong Hyo Lee; Eun Young Jang; Hee Young Kim; Sun-Mi Choi; Scott C. Steffensen; Chae Ha Yang (Psychopharmacology, 2012)

Elevated mercury exposure and neurochemical alterations in little brown bats (Myotis lucifugus) from a site with historical mercury contamination - Dong-Ha Nam; David Yates; Pedro Ardapple; David C. Evers; John Schmerfeld; Niladri Basu (Ecotoxicology, 2012)

Mapping the irrigated rice cropping patterns of the Mekong delta, Vietnam, through hyper-temporal SPOT NDVI image analysis - Thi Thu Ha Nguyen; C. A. J. M. De Bie; Amjad Ali; E. M. A. Smaling; Thai Hoanh Chu (International Journal of Remote Sensing, 2012)

In vitro degradation of zearalenone by Bacillus subtilis - K. J. Cho; J. S. Kang; W. T. Cho; C. H. Lee; J. K. Ha; Kyung Bin Song (Biotechnology Letters, 2010)

Genetic analysis of avian influenza A viruses isolated from domestic waterfowl in live-bird markets of Hanoi, Vietnam, preceding fatal H5N1 human infections in 2004 - Samadhan J. Jadhao; Doan C. Nguyen; Timothy M. Uyeki; Michael Shaw; Taronna Maines; Thomas Rowe; Catherine Smith; Lien P. T. Huynh; Ha K. Nghiem; Diep H. T. Nguyen; Hang K. L. Nguyen; Hanh H. T. Nguyen; et al. (Archives of Virology, 2009)

Structural analysis of enniatin H, I, and MK1688 and beauvericin by liquid chromatography-tandem mass spectrometry (LC-MS/MS) and their production by Fusarium oxysporum KFCC 11363P - H.-H. Song; H.-S. Lee; G.-P. Lee; S.-D. Ha; C. Lee (Food Additives & Contaminants: Part A, 2009)

Identification and sequence analysis of potyviruses infecting crops in Vietnam - C. Ha; P. Revill; R. M. Harding; M. Vu; J. L. Dale (Archives of Virology, 2008)

Design and application of two novel degenerate primer pairs for the detection and complete genomic characterization of potyviruses - C. Ha; S. Coombs; P. A. Revill; R. M. Harding; M. Vu; J. L. Dale (Archives of Virology, 2008)

Germ-line DNA copy number variation frequencies in a large North American population - George Zogopoulos; Kevin C. H. Ha; Faisal Naqib; Sara Moore; Hyeja Kim; Alexandre Montpetit; Frederick Robidoux; Philippe Laflamme; Michelle Cotterchio; Celia Greenwood; Stephen W. Scherer; Brent Zanke; et al. (Human Genetics, 2007)

Hydrophilicity dependent budding and secretion of chimeric HIV Gag-V3 virus-like particles - Lizhong Luo; Yan Li; Soon Duck Ha; C. Yong Kang (Virus Genes, 2007)

Elucidation of the mechanisms underlying the angiogenic effects of ginsenoside Rg1 in vivo and in vitro - Patrick Y. K. Yue; Daisy Y. L. Wong; W. Y. Ha; M. C. Fung; N. K. Mak; H. W. Yeung; H. W. Leung; Kelvin Chan; L. Liu; T. P. D. Fan; Ricky N. S. Wong (Angiogenesis, 2007)

Mutation analysis of hepatitis B virus promoters in chronically infected children - J. W. Sohn; C. W. Lee; J. H. Lee; K. C. Lee; C. S. Son; J. W. Lee; Y. M. Ha-Lee (Archives of Virology, 2005)

Expression of mRNA Encoding Interleukin (IL)-10, IL-12p35 and IL-12p40 in Lungs from Pigs Experimentally Infected with Actinobacillus pleuropneumoniae - W.-S. Cho; K. Jung; J. Kim; Y. Ha; C. Chae (Veterinary Research Communications, 2005)

The complete nucleotide sequence of two distinct geminiviruses infecting cucurbits in Vietnam - P. A. Revill; C. V. Ha; S. C. Porchun; M. T. Vu; J. L. Dale (Archives of Virology, 2003)

Characterisation of Rep-encoding components associated with banana bunchy top nanovirus in Vietnam - K. E. Bell; J. L. Dale; C. V. Ha; M. T. Vu; P. A. Revill (Archives of Virology, 2002)

Organochlorine Contaminant Exposure and Reproductive Success of Black-Crowned Night-Herons ( Nycticorax nycticorax ) Nesting inBaltimore Harbor, Maryland - B. A. Rattner, P. C. McGowan, J. S. Ha (Archives of Environmental Contamination and Toxicology, 2001)

A candidate gene approach identified phytoene synthase as the locus for mature fruit color in red pepper (Capsicum spp.) - J. H. Huh; B. C. Kang; S. H. Nahm; S. Kim; K. S. Ha; M. H. Lee; B. D. Kim (Theoretical and Applied Genetics, 2001)

Production of transgenic tall fescue and red fescue plants by particle bombardment of mature seed-derived highly regenerative tissues - M.-J. Cho; C. D. Ha; P. G. Lemaux (Plant Cell Reports, 2000)

Crystal structure of bullfrog M ferritin at 2.8 Å resolution: analysis of subunit interactions and the binuclear metal center - Y. Ha; Dashuang Shi; George W. Small; Elizabeth C. Theil; N. M. Allewell (JBIC Journal of Biological Inorganic Chemistry, 1999)

Untersuchungen zum UV-photometrischen Nachweis der kurzzeitig zurckliegenden Einnahme therapeutischer und suicidaler Dosen von Carbromal (Adalin) im Harn - C. Schtz; Y. D. Ha; D. Post; H. Schtz (Archives of Toxicology, 1974)